Impact of the Peace Education Program on the Social Behavior of Pre-Schoole children in the Sultanate of Oman - Rashid Al Mushaqiri, Mahfouda; Bin Ishak, Zahari; Muin Ismail, Wail (Opción, 2019)
Education is a necessary process for both the individual and the community, as it is necessary for the human being to preserve it, direct its instincts, organize emotions and develop its tendencies in a way that is commensurate with the culture. The stage of pre-school education is one of the most important stages experienced by man in his life in which the first features of them personality are formed. Pre-school children are affected by the apparent violence around them, and the programs to which they are exposed are often based on competition and evaluation, and lack of interest in the development of self-concept and self-confidence. In addition, edu- cation programs at this stage are also devoid of peace education. Many problems come from the lack of internal peace in the human being, first and foremost chil- dren. Furthermore, the present study provided a peace education program (PEP) for pre-school children aged (4 - 6) years in Oman. Where the program contains (28) training sessions are offered within (15) weeks at the rate of one hour per session. The researcher used a pictorial estimate, the behavior of the children was measured before and after the experiment, where the researcher adopted the experimental method, the sample consisted of (40) children in the experimental group and (40) children in the control group.